Fresh perspectives on India`s organizational dimension - Gupta, Vipin; Chatterjee, Samir Rajan; Maurya, Alka (New Jersey World Scientific Publishing Co. Pte. Ltd., 2025)
This edited book collects several deep insights into the trends and transitions in work organizations in India. It explores significant themes highlighting areas such as globalisation, digitisation, social and managerial transformations. Chief among its chapters are a number of collaborative studies on the potential impact of societal and technological changes on the design, operation as well as strategic platforms, which add richness to the volume.